People in Good Corporate Governance: Position, Relation, and Civility Scheme - Imam Samroni (Millah: Journal of Religious Studies, 2007)
The relationship between state executor, business actor, and people or social order that enter Good Corporate Governance and Corporate Social Responsibility on an agenda is not necessarily in a mutual accord. This paper offers three schemes in strengthening the position and relationship of the people or social order among other stakeholders. First is the attitude toward neo-liberalism, which is the scheme to prepare the people or the social order using future research in managing the future. Second is the scheme of democracy choice that has been a must in the reason economic-politic conditions. And thirdly, the attitude toward “memetic engineering,” which is the scheme to develop populist values parallel with nation plurality that they are accepted and are not constantly put in a contradiction.Keyword: GCG, CSR, neo-liberalism, people, civility